NILAI TAMBAH PRODUKSI KAYU LAPIS, INDAH DARI BEBERAPA PERUSAHAAN DI SUMATRA UTARA - Rachman Effendi; Suwidji Basuki (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
One of the products that can be produced from secondary process of plywood is fancy plywood. The product is usually constructed by overlaying plywood with fancy veneer or other material with nice decorative appearance. This process will add extra value to the final product intern of selling price as compared with ordinary plywood. In this study fancy. plywood is constructed by overlaying plywood with fancy veneer of jati, mahoni and rengas.Added value of fancy plywood (from plywood)in three ply mills in North Sumatra amounted to Rp.1,032,749,600 in one year resulted from 5141 cu.m of plywood. The value is accounted for production factors with the following proportion: 17.73 % from depreciation factor, 21.94 % from labour cost, and 60.33 % from profit, taxes, and others. The employment created by each factory is 48 workers which are equal to 13,920 man days per year.